THE EMERGENCE-THEORETICAL ASPECTS OF DIALOGUE IN EDUCATION - Akhmedov B.A.; Khimmataliyev D.O. (Sciental Journals Publishing, 2024)
The article presents the justification of the actual use of dialog in modern education, its unique potential for the development of personality, for demonstrating dialogical unity, equality of partners, the right to one's own opinion. The author considers the fundamental ideas of outstanding thinkers of the past and present, which allow to define the essential features of dialog and its potential in education. It is proposed to develop the foundations of dialogical pedagogy as a science of human development in the conditions of forming relationships to the world, to other people and to oneself.
Keywords: Dialogue; Antiquity; Socrates; Education; Subject relations; Dialogic Pedagogy